1975
DOI: 10.1128/iai.11.1.92-94.1975
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of aleutian disease of mink: identification of nonpersistent infections

Abstract: Aleutian disease virus usually produces a persistent infection and progressive immune complex disease in mink of the Aleutian genotype. Study of Aleutian disease virus infection in non-Aleutian mink showed that about one-quarter developed nonpersistent infections by the virus, and that the nonpersistence was not genetically determined by the host. The nonpersistently infected mink developed only a transient elevation of serum gamma globulin, and much lower specific Aleutian disease virus antibody titers than p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
27
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 7 publications
6
27
0
Order By: Relevance
“…The relation of the virus strain to such persistent infection without disease is not clear. In one study, viremia was not detected in subclinically infected pastel mink 120 days after they had been inoculated intraperitoneally with the Utah-1 strain (20). Whether virus was still present in other tissues was not determined.…”
Section: 'mentioning
confidence: 99%
See 1 more Smart Citation
“…The relation of the virus strain to such persistent infection without disease is not clear. In one study, viremia was not detected in subclinically infected pastel mink 120 days after they had been inoculated intraperitoneally with the Utah-1 strain (20). Whether virus was still present in other tissues was not determined.…”
Section: 'mentioning
confidence: 99%
“…Nor have specific host attributes been identified that allow infection to result in overt disease in some mink and not in others. Certainly susceptibility or resistance of pastel mink to AD does not have a simple genetic explanation (15,20). And despite the profound constitutional differences between pastel and sapphire mink attributable to the pleiotropic effects of the Aleutian gene in sapphire mink (18,19,24), the basis for the generally greater susceptibility of sapphire mink to AD is not understood (21).…”
Section: 'mentioning
confidence: 99%
“…Mink that are homozygous for the Aleutian gene are the most severely affected and usually die from immune complex glomerulonephritis or arteritis within 5 months of infection (7,11). Other genetic types of mink may develop progressive disease, or may have a persistent, but inapparent, infection, or may clear the virus and recover (1)(2)(3)17). The pathogenesis of ADV infection in mink has been reviewed in detail (10,22).…”
mentioning
confidence: 99%
“…Of interest for the present review is an economically important common disease due to a parvovirus causing chronic infection and disease in farm raised minks, first recognised in 1956 in minks homozygous for the Aleutian (blue) gene and hence the name Aleutian disease (AD). It was subsequently found that other genetic types of mink could develop AD but infection of non-Aleutian mink is not uniformly persistent [110][111][112]. The causative parvovirus (ADV) also infects other mustelids particularly skunks and ferrets; in pet ferrets AD is an emerging disease and the virus appears to have adapted to the species and a strain of virus (the ADV-F) is only pathogenic in ferrets.…”
Section: Diseasementioning
confidence: 99%